Involvement of purple acid phosphatase gene into nitrogen uptake of oil palm (Elaeis guineensis) - SIGIT DWI MARYANTO; ZULFIKAR ACHMAD TANJUNG; ROBERDI ROBERDI; WIDYARTINI MADE SUDANIA; PUJIANTO PUJIANTO; HAIRINSYAH HAIRINSYAH; CONDRO UTOMO; TONY LIWANG (Society for Indonesian Biodiversity, 2021)
Abstract. Maryanto SD, Tanjung ZA, Roberdi, Sudania WM, Pujianto, Hairinsyah, Utomo C, Liwang T. 2021. Involvement of purple acid phosphatase gene into nitrogen uptake of oil palm (Elaeis guineensis). Biodiversitas 22: 1385-1390. Nitrogen is the most important nutrient element in terms of plant growth. Plant purple acid phosphatases (PAPs) are known to participate in the phosphate (Pi) acquisition and utilization. Moreover, PAP gene plays an important role in nitrogen fixation. A single nucleotide polymorphism (SNP) was previously detected in the exon 7 of EgPAP3, based on SNP mining analysis of oil palm (Elaeis guineensis Jacq.). genome database. This study was aimed to obtain a Cleaved Amplified Polymorphic Sequences (CAPS) marker based on SNP within EgPAP associated with efficient nitrogen uptake oil palm progenies. Primer pairs were designed and used for PCR amplification of 3 oil palm progenies that showed low N-content, 3 progenies with moderate N-content, and 3 progenies with high N-content. The amplicon was purified prior to single-pass DNA sequencing analysis. Based on Pearson’s chi-square and odds ratio statistical analysis, the SNP has strong positive correlation with the phenotype. The SNP is located at chromosome 13 with a distance of 17.7771 cM from start codon. The sequencing analysis revealed that three progenies with high N-content samples had GG allele motif, while moderate N-content progenies had GA allele and low N-content progenies had AA allele motifs respectively. In addition, a restriction site of NIaIV was found to be adjacent to the SNP location, thus the PCR products of all samples were digested with NIaIV restriction enzyme. NIaIV was able to distinguish between high, medium and low efficient DNA samples. Whole high N-content progenies with GG allele motifs were undigested indicating a single band size of 670 bp identical to the untreated PCR product (control). Moderate N-content progenies produced a 670 bp, 550 bp, and 120 bp bands because of digested by NIaIV. Low N-content progenies also resulted in double bands of 550 bp and 120 bp due to digested by NIaIV. Furthermore, NIaIV restriction enzyme was applied to digest other 54 oil palms DNA samples with unknown genotypes. Whole GG samples were consistently shown to have single band, GA and AA samples were also consistent in producing two bands with different lengths. Based on this result, CAPS marker based on SNP in EgPAP3 was successfully developed to screen between high and low efficient N-uptake of oil palm progenies.